The improvement of deformability in AA7075 alloy through cryogenic treatment and its correlation with microstructural evolution and FE modelling - Suwaree Chankitmunkong; Dmitry Eskin; Ussadawut Patakham; Wares Chancharoen; Saran Seehanam; Chaowalit Limmaneevichitr; Phromphong Pandee (Scientific Reports, 2024)
CuMg phase influenced the deformation texture of the tested aluminum alloy, resulting in more elongated grains and fine sub-grains after deformation at cryogenic temperatures, due to the hindered recrystallization. Microstructure evolution after deformation at room and cryogenic temperatures was investigated using EBSD technique to characterize texture and recrystallized grains. The results indicated that the spacing of the high-angle grain boundaries (HAGBs) in the sample deformed at room temperature was slightly larger than in the cryogenically treated sample. The alloy deformed at the cryogenic temperature exhibited a higher strain hardening exponent (n = 0.35) compared to room temperature deformation (n = 0.25). Furthermore, finite element analysis supported the experimental findings, showing that the Plastic Equivalent Strain (PEEQ) of the model tested at cryogenic temperature was higher than at room temperature, attributed to grain refinement during low-temperature deformation. The calculated effective stress responses at cryogenic temperatures for the investigated flow stress aligned well with the experimental results. These new aspects and mechanisms of deformation of aluminum alloys at cryogenic temperatures can improve the formability of high-strength alloys in the future production of more complex and integrated lightweight components.
Keywords: Metal Alloys Wear and Properties; Metallurgy and Material Forming; Microstructure and mechanical properties